The Neurotheology of Contemporary Spirituality: A Review Essay of The Varieties of Spiritual Experience - Nenadalová, Jana (Journal for the cognitive science of religion, 2021)
The Varieties of Spiritual Experience: 21st Century Research and Perspectives, by David B. Yaden and Andrew B. Newberg. Oxford: Oxford University Press, 2022. x + 430 pages, £26.49. ISBN: 9780190665678